4‐1: Development of Ultra‐Large 95inch 8K 120Hz OLED Display. Issue 1 (28th June 2022) - Wu, Zhongyuan; Li, Yongqian; Yan, Liangchen; Ye, Lankai; Peng, Yuqing; Shih, Huaiting; Yu, Jianwei; Dong, Xue
Abstract : We presented so far the world's first largest 95inch 8K OLED display. To develop this OLED display with ultra‐large size and ultra‐high resolution, we have employed the new pixel structure, high speed driving technology and advanced compensation technique. The stunning ultra‐large OLED display not only reproduce the high quality image, but also create an immersive experience that allow the audience to feel as if they were a part of the scene.